EFEKTIVITAS PENGGUNAAN MEDIA FLIP BOOK BERBASIS CANVA TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN IPAS SISWA KELAS IV SDN KOMPLEKS IKIP MAKASSAR - Sepriyanti Nurul Ma’wiah; Erma Suryani Sahabuddin; Hardianto Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning motivation of fourth-grade students in Natural and Social Sciences (IPAS) at SDN Kompleks IKIP Makassar, indicated by low participation and limited use of instructional media. The study aimed to determine the effectiveness of Canva-based flip book media in improving students’ learning motivation. This research employed a quantitative approach with a quasi-experimental design using a Nonequivalent Control Group Design. The subjects consisted of 40 students from two classes, namely the experimental and control classes. The instruments used were a learning motivation questionnaire administered before and after treatment and an observation sheet to assess the implementation of the media. Data were analyzed using descriptive statistics and independent sample t-test. The results showed a significant difference between students taught using Canva-based flip book media and those taught using conventional methods. Therefore, Canva-based flip book media is effective in improving students’ learning motivation in IPAS.